Risk factors of perioperative mortality from complicated peptic ulcer disease in Africa: systematic review and meta-analysis. Issue 1 (17th February 2020) - Peiffer, Sarah; Pelton, Matthew; Keeney, Laura; Kwon, Eustina G; Ofosu-Okromah, Richard; Acharya, Yubraj; Chinchilli, Vernon M; Soybel, David I; Oh, John S; Ssentongo, Paddy
Abstract : Introduction: In 2013, peptic ulcer disease (PUD) caused over 300 000 deaths globally. Low-income and middle-income countries are disproportionately affected. However, there is limited information regarding risk factors of perioperative mortality rates in these countries. Objective: To assess perioperative mortality rates from complicated PUD in Africa and associated risk factors. Design: We performed a systematic review and a random-effect meta-analysis of literature describing surgical management of complicated PUD in Africa. We used subgroup analysis and meta-regression analyses to investigate sources of variations in the mortality rates and to assess the risk factors contributing to mortality. Results: From 95 published reports, 10 037 patients underwent surgery for complicated PUD. The majority of the ulcers (78%) were duodenal, followed by gastric (14%). Forty-one per cent of operations were for perforation, 22% for obstruction and 9% for bleeding. The operations consisted of vagotomy (38%), primary repair (34%), resection and reconstruction (12%), and drainage procedures (6%). The overall PUD mortality rate was 6.6% (95% CI 5.4% to 8.1%). It increased to 9.7% (95% CI 7.1 to 13.0) when we limited the analysis to studies published after the year 2000. The correlation was higher between perforated PUD and mortality rates (r=0.41, p<0.0001) than for bleeding PUD and mortality rates (r=0.32, p=0.001). Non-significant differences in mortality rates existed between sub-Saharan Africa (SSA) and North Africa and within SSA. Conclusion: Perioperative mortality rates from complicated PUD in Africa are substantially high and could be increasing over time, and there are possible regional differences.